INOVASI PEMBELAJARAN IPA "STRUKTUR BUMI DAN TATA SURYA" MELALUI SIMULASI QREATIF EDUCATIVE DAN KUIS QUIZLET UNTUK KELAS VI SD - Sharla Martiza; Ika Putra Viratama (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
Science learning in elementary schools frequently encounters pedagogical challenges, particularly when teaching abstract concepts such as Earth structure and the solar system. Traditional instructional methods that rely heavily on verbal explanations and textbooks often limit students’ conceptual understanding and engagement. This study aims to analytically describe an innovation in science learning through the integration of Qreatif Educative simulations and Quizlet-based interactive quizzes for sixth-grade elementary school students. This research adopts a qualitative approach using a library research design. Data were collected from scientific journals, academic books, and relevant research articles indexed in Google Scholar and DOAJ. The collected data were analyzed systematically through content analysis stages, including data reduction, categorization, theoretical synthesis, and analytical interpretation. The findings indicate that Qreatif Educative simulations facilitate concrete visualization of abstract scientific concepts, thereby enhancing students’ conceptual comprehension. Furthermore, Quizlet quizzes function as formative assessment tools that increase student motivation, learning engagement, and retention through game-based evaluation. In conclusion, this learning innovation effectively supports student-centered and meaningful science learning at the elementary school level.